2020
DOI: 10.1080/02640414.2020.1835221
|View full text |Cite
|
Sign up to set email alerts
|

Values and clean sport

Abstract: The spirit of sport which encompasses intrinsic values associated with sport participation, is core to the World Anti-Doping Agency's (WADA) strategy for doping prevention. The contribution of these values in clean sport has yet to be established. In this study, athletes rated the importance of spirit of sport values (WADA, 2015) and sport values (Lee et al., 2000(Lee et al., , 2008 and indicated their clean sport likelihood in a hypothetical scenario. Clean sport likelihood was positively predicted by the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 46 publications
3
26
0
Order By: Relevance
“…Since the publication of those two reviews, further studies have investigated the relationship between an athlete's values and beliefs, and their doping intentions. A recent study (Mortimer et al, 2020) reported that athletes with a strong moral identity are less likely to use banned substances, and similar findings have also been reported in several other recent studies across various sporting populations (Boardley et al, 2014;Allen et al, 2015;Madigan et al, 2016;Mallia et al, 2016;Kavussanu and Ring, 2017).…”
Section: Values Beliefs and Attitudessupporting
confidence: 84%
“…Since the publication of those two reviews, further studies have investigated the relationship between an athlete's values and beliefs, and their doping intentions. A recent study (Mortimer et al, 2020) reported that athletes with a strong moral identity are less likely to use banned substances, and similar findings have also been reported in several other recent studies across various sporting populations (Boardley et al, 2014;Allen et al, 2015;Madigan et al, 2016;Mallia et al, 2016;Kavussanu and Ring, 2017).…”
Section: Values Beliefs and Attitudessupporting
confidence: 84%
“…Values ranked the lowest were “excellence in performance” (shared by athletes in all countries but Russia) and “courage” (universally agreed among all five countries). Our results broadly align with previously recorded rankings of the Spirit of Sport values in Australia, Greece (Mazanov et al, 2019 ), and in the UK (Mortimer et al, 2020 ). Courage and excellence in performance appear to be universally unimportant, whereas respect and health valued the most—at least in the countries investigated to date.…”
Section: Discussionsupporting
confidence: 92%
“…To surpass this goal and to better the provision of anti-doping education for athletes, it is important to understand how these individuals from different countries prioritize their values, both in general, everyday life and within their sporting world. It is also critical to understand the impact that the values which underpin the Spirit of Sport (WADA, 2021a ) have on an athletes' beliefs of the importance of clean sport and their contribution to maintaining clean sport (Mortimer et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations